Effects of the Installation Method, Loading Condition, and Failure Mechanism on the Behavior of Suction Piles under Monotonic Horizontal Loading - Juhyung Lee; Jinung Do (Journal of Marine Science and Engineering, 2021)
A suction pile is a promising option when floating offshore structures are deployed at deep and distant locations. A suction pile is typically used for the foundation system of a mooring system subjected to horizontal loading with a load inclination. In this study, the effects of installation method, loading position, and load inclination on the behavior of a suction pile under monotonic horizontal loading were evaluated via large-scale soil chamber testing. A series of horizontal load tests were performed by varying the loading position at pile embedded lengths of 1/4, 1/2, 2/3, and 3/4. A horizontal load test with a load inclination of 20° was conducted and compared with that of a load inclination of 0°. The failure mechanism of the suction piles under monotonic horizontal loading was assessed via particle image velocimetry (PIV) analysis. The movement of the suction pile during monotonic horizontal loading was elucidated in terms of the horizontal displacement, vertical displacement, and rotation angle. The results of this study show apparent differences between jacking and suction-installed piles and piles under different loading conditions. The PIV analysis shows that the rotational behavior under monotonic horizontal loading can be a critical point to affect the horizontal resistance of the suction pile.